Editor’s Note - Noonan, Ken (Journal of the Pediatric Orthopaedic Society of North America, 2020)
Ernest Codman MD (Codman’s Triangle, Codman’s Shoulder Exercises) was a Harvard surgeon who first proposed to his colleagues in the early 1900’s that it might be a good idea to study and record the after-effects from surgery. He felt that the “End Result” should be recorded in order to improve care and results could be made public thus allowing patients to make informed decisions when selecting a provider. Considered the founder of outcomes research and studies for quality; he wasn’t exactly a favorite of his peers who felt that knowing how patients fared might affect their livelihood. Eventually he lost his Harvard appointment as result of his fervent desire to improve quality in the face of stiff peer pressure. Despite being ostracized for the majority of his career, he was a founding member of the American College of Surgeons and his focus on quality eventually led to today’s Joint Commission on Accreditation of Hospitals. It’s astounding that early physicians were afraid to learn and document their outcomes and equally amazing how far we have come in the evolution of outcomes research. We have evolved from simply recording the “End Result” as Codman advised; to keeping track of things like radiographic results. We now collect patient reported outcome measures as a means to understand methodology and the importance of evidence. We recognize a broader understanding that sustainable quality requires standardization and structure including checklists and guidelines. Quality. Safety. Value. If you are like me, prior to 2011-2012; these were words that I used in my professional life to describe efforts to provide excellent care with low complication rates and as cheaply as possible. Yet while we were practicing pediatric orthopaedics with these goals in mind, POSNA was on the forefront of expanding what these words mean to us now. Kevin Shea writes in this edition of JPOSNA about the history of the QSV initiative and its current directions at the patient level, system level and for all of society. Our President Michael Vitale, will let us peek into new POSNA initiatives to improve safety for our patients. In this edition of JPOSNA we are fortunate to have FOUR papers related to improving systems of care, safety and attempts to document the value of what we do. JPOSNA hopes to facilitate the pioneering work of Ernest Codman and POSNA; and we endeavor to become the destination for quality improvement manuscripts that seek to document the Value of Safe, High Quality Care for children with orthopaedic disorders.